Bachelor Hall - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet, likely intended for a female reader, describes how to decorate a man's room or apartment. Discusses design aspects that are strictly masculine, and identifies decorative qualities a man would desire. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Stereotypes (Social psychology); Paint materials; Sexism; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Interior decoration